Study on cerebral vascular image of spectral domain optical coherence tomography with compressive sensing (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
We propose a novel compressed sensing method to retrieve cerebral vascular image for spectral-domain optical coherence tomography (SD OCT). The compressed sensing method based on l1 norm minimization is applied to reconstruct each A-scan data. The proposed method uses about 25% of the total data as required in traditional SD OCT to reconstruct the cerebral angiograpy. Therefore this method is favorable for high speed imaging for cerebral angiograpy. It is shown that the proposed method can achieve better performance of axial resolution and higher signal-to-noise ratio (SNR) as compared with the conventional methods.